Indirect Determination of Sulfamethazine Sodium by Cu2+ Complexation Extraction and Flame Atomic Absorption Spectrophotometry - Wei, Xiaoling; Li, Dongmei; Du, Liangwei; Gong, Qi (Asian Journal of Chemistry, 2010)
Sulfamethazine (SM2) salt and Cu2+ combined to form 2:1 complex in the solution of pH 5.0- 6.5. After the complex was extracted with chloroform, the absorbence of Cu2+ remaining in water phase was determined by flame atomic absorption spectrometry (FAAS). It was found that the absorbancy difference (ΔA) of Cu2+ in raffinate solution of reagent blank solution and sample solution increased linearly with the concentration of sulfamethazine. Under the optimum conditions, the linear range of sulfamethazine was 14.6-144.1 mg L-1, the linear regression equation was ΔA = 0.0025c - 0.0046 (r = 0.9991), the detection limit for sulfamethazine was 5.6 mg L-1 and the recovery was 99.3-99.6 %. This method was used to determine the sulfamethazine sodium injection samples with satisfactory results.